2013
DOI: 10.2214/ajr.12.10217
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Volume of Carotid Artery Plaque and Its Subcomponents and the Volume of White Matter Lesions in Patients Selected for Endarterectomy

Abstract: The cerebral WML volume and the total volume of the plaque are correlated. The amount of fat within the plaque is an additional risk factor, whereas the calcified component seems to be protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…This is an interesting point in our opinion, because this aspect represents a significant difference compared to the local effect of atherosclerosis at the level of carotid arteries where the percentage of lipid components (and not only the volume) seems to be a trigger toward the plaque's vulnerability. 32 The Mann-Whitney test assessed also the total plaque volume, the subcomponents volume, and the percentage in the groups with and without CMBs, and we found that there is a statistically significant difference in volume of all the subcomponents with the most important value in the lipid components.…”
Section: Discussionmentioning
confidence: 69%
“…This is an interesting point in our opinion, because this aspect represents a significant difference compared to the local effect of atherosclerosis at the level of carotid arteries where the percentage of lipid components (and not only the volume) seems to be a trigger toward the plaque's vulnerability. 32 The Mann-Whitney test assessed also the total plaque volume, the subcomponents volume, and the percentage in the groups with and without CMBs, and we found that there is a statistically significant difference in volume of all the subcomponents with the most important value in the lipid components.…”
Section: Discussionmentioning
confidence: 69%
“…They planned a systematic evaluation of 50 patients, enrolled to carotid-endo-arterectomy (CEA) who underwent firstly to CTA to well define stenosis degree, composition of carotid plaque and predict its behavior as stable or unstable on the basis of presence or not of fibro-calcific components; and then to brain MRI. The results showed a critical association between total carotid artery plaque volume and the onset of WMH areas mainly located in cerebral areas perfused by MCA in spite of anterior (ACA) or posterior cerebral artery (PCA) [42]. These behavioral differences relate to frequent variations and subsequently different compartmentalization of vascular blood-flow along Circle of Willis (COW) demonstrating lower risk of stroke and transient ischemic attacks among people who have effective collateral circles, while higher risk in those who have poor collateral circles [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, although carotid atherosclerosis has been demonstrated to have a strong relationship with stroke and small-vessel disease, its association with LA was controversial, 29,30 but some years later, there was a shift in the point of view because other studies, mainly performed with MRI technique, found an association between the presence of the atherosclerotic load in the carotid artery plaque and the presence and severity of white matter changes. 31,32 However, the association between atherosclerosis and white matter pathology was not clear because it is well known that there are several types of atherosclerosis, 33 and some authors found an association between the presence of calcium components and LA, 34 whereas others found an association between lipid components and LA, 13 which are 2 completely different types of plaque. Regarding this point, it would be important to remember that the pathogenesis of atherosclerosis and cerebral small-vessel disease is associated with inflammatory process, 35,36 and also plays a role in the response to ischemic events that result from atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, recent published papers have linked this condition to large-vessel atherosclerosis. [12][13][14] Because of the potential association between carotid artery pathology and LA, we tried to explore the potential correlation between the volume of LA and the carotid artery plaque attenuation by considering the different HU levels owing to the different keV selection obtainable with the dual-energy scanner.…”
Section: Introductionmentioning
confidence: 99%